ESTIMASI REGRESI NADARAYA WATSON DENGAN KERNEL ORDER TAK HINGGA - , Maria Suci Apriani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The function estimation of r(Xi) in linier regretion which is drawn near with nonparametric approach is done if there is no assumption about regretion function form of r(Xi). One of techniques used is smoothing technique with kernel. Function of rË ï¨ xï© can be reduced to be o(hk) with choosing the kernel that has the bigger order from the amount of differensial number. Therefore, a kernel which has âinfinite orderâ can be determined.